Numerical modelling of masonry-infilled reinforced concrete frames : model calibration and parametric study - Akhoundi, Farhad (2014)
Generally two methods are proposed for analyzing the infilled frames; Micro modelling approach which finite element method is used to take into account local effects in detail and Macro modelling approach which is a very simplified method that takes into account the global behavior of the structure by replacing the infill with diagonal strut. In the present study a numerical analysis is carried out on a one bay one storey reinforced concrete frame with masonry infill under in-plane loading by using finite element modelling through the DIANA software. The numerical model was calibrated based on experimental results and then a parametric study was carried out, taking into account variation of material properties of infill and its height to length ratio. It is concluded that compressive strength and height to length ratio of the masonry infill has dominant role on the in-plane behavior of these types of masonry infilled frames. Increasing the compressive strength of the masonry enhances the lateral strength of the infilled frames while increasing the height to length ratio of the infill panel results in decrease of their lateral strength and initial stiffness.